Welcome :: Homework Help and Answers :: Mathskey.com
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,356 questions

17,804 answers

1,438 comments

35,964 users

Can someone help me & please give me the answers to these 5 problems?

+2 votes

 

Can someone help me & please give me the answers to these 5 problems?

1.) If f(x)=3x+9 , what is f-1(x)? 

A: f-1(x)=1/3x-3 
B: f-1(x)=-1/3x-9
C: f-1(x)=-3x-9
D: ff-1(x)=1/3x+9

2.) If f(x)=3/x and g(x)=3x , which of the following statements is true? 

A: (f · g)(2)=2 
B: (g · f)(2)=0
C: (f · g)(9)=1
D: (g · f)(-9)=-1

3.) If f(x) and g(x) are inverse functions or each other, which of the following statements is true? 

A: f(x)/g(x)=1 
B: f(x)=-g(x)
C: (f · g)(x)=1
D: (g · f)(x)=x

4.) If f(x)=4x-2 and g(x)=x+1, which of the following statements are true? 

A: (f · g)(x)=4x^2+2x-2 
B: (f · g)(x)=4x+2
C: (g · f)(x)=2x-2
D: (g · f)(x)=x

5.) If f(x)=2√x and g(x)=9x, which of the following statements is true? 

A: (g · f)(x)=√18x 
B: (f · g)(x)=2√3x
C: (f · g)(x)=6√x
D: (g · f)(x)=x

 

asked Jan 2, 2013 in ALGEBRA 2 by homeworkhelp Mentor

5 Answers

+5 votes

1 )  f(x)=3x+9

Let f(x)= 3x+9 = y

f(x) = y and 3x+9 = y

x = ƒ−1(y) -------------> (1)

3x + 9 = y

Subtract 9 from each side

3x = y - 9

x = (y - 9) / 3 ----------->(2)

From (1) and (2)

ƒ−1(y) = (y - 9) / 3

Substitute with y by x

ƒ−1(x) = (x - 9) / 3

ƒ−1(x) = (1/3)x - 3

The option A is the right choice

 

 

 

 

answered Jan 2, 2013 by ashokavf Scholar
+5 votes

4)Given functions are f(x)=4x-2 and g(x)=x+1

(f · g)(x) = [(4x-2)(x+1)]

             = [(4x)(x+1) - (2)(x+1)]

             = [(4x^2+4x) - (2x+2)]

            =  [(4x^2+4x-2x-2)]

(f · g)(x)=  [(4x^2+2x-2)]

The option A is correct.

 

answered Jan 2, 2013 by friend Mentor
0 votes

2) f(x ) = 3 / x  and g(x ) = 3x.

A: (f · g)(2)

= f(2) * g(2)

= (3/2) * 3(2)

= (3/2) * 6

=

Therefore (f · g)(2) ≠  2.

B: (g· f)(2)

= g(2) * f(2)

= (3/2) * 3(2)

= 9 

Therefore  (g· f)(2) ≠ 0. 

C: (f · g)(9 )

= f(9) * g(9)

= (3/9) * 3(9)

= (1/3) * 27

=

Therefore (f · g)(9) ≠  1

D: (g· f)(-9)

= g(-9) * f(9)

= (3/-9) * 3(-9)

= (-1/3) * -27

= 9 

Therefore (g· f)(-9) ≠ -1

None of them is True.

answered Jun 26, 2014 by joly Scholar
0 votes

3) Let the inverse functions be f(x ) = x2 and g(x ) = √ x.

A: f(x ) / g(x )

= x2 / √ x

= x3/2

Therefore f(x ) / g(x ) ≠  1.

Therefore the statement is False.

B: f(x )  ≟  -g(x )

x2   ≟  - √ x

x2  ≠ - √ x

Therefore f(x )  ≠  -g(x ).

Therefore the statement is False.

C: (f · g)(x )

= f(x ) * g(x )

= x2 * √ x

= x5/2 

Therefore (f · g)(x ) ≠  1.

Therefore the statement is False.

D: (g· f)(x )

= g(x ) * f(x )

= x * x2

= x5/2 

Therefore (g· f)(-9) ≠ x.

Therefore the statement is False.

answered Jun 26, 2014 by joly Scholar
0 votes

5) Let the inverse functions be f(x ) = 2√x and g(x ) = 9x.

A: (g· f)(x )

= g(x ) * f(x )

= 9x * 2x

= 18x3/2 

Therefore (g· f)(x )√18x.

Therefore the statement is False.

B: (f · g)(x )

= f(x ) * g(x )

= 2x * 9x

= 18x3/2

Therefore (f · g)(x ) ≠  2√3x.

Therefore the statement is False.

C: (f · g)(x )

= f(x ) * g(x )

= 2x * 9x

= 18x3/2

Therefore (f · g)(x ) 6√x.

Therefore the statement is False.

D: (g· f)(x )

= g(x ) * f(x )

= 9x * 2x

= 18x3/2 

Therefore (g· f)(x )x.

Therefore the statement is False.

 

answered Jun 26, 2014 by joly Scholar

Related questions

asked Nov 25, 2014 in CALCULUS by anonymous
asked Nov 25, 2014 in CALCULUS by anonymous
asked Nov 4, 2014 in ALGEBRA 2 by anonymous
...